A Consensus Statement on establishing causality, therapeutic applications and the use of preclinical models in microbiome research - Metwaly, Amira; Kriaa, Aicha; Hassani, Zahra; Carraturo, Federica; Druart, Celine; Pinto, Federica; Asnicar, Francesco; Segata, Nicola; Morozova, Vitalina; Sarathi, Arjun; Arumugam, Manimozhayan; Boucher, Katy; et al. (Nature Reviews Gastroenterology & Hepatology, 2025)
The gut microbiome comprises trillions of microorganisms and profoundly influences human health by modulating metabolism, immune responses and neuronal functions. Disruption in gut microbiome composition is implicated in various inflammatory conditions, metabolic disorders and neurodegenerative diseases. However, determining the underlying mechanisms and establishing cause and effect is extremely difficult. Preclinical models offer crucial insights into the role of the gut microbiome in diseases and help identify potential therapeutic interventions. The Human Microbiome Action Consortium initiated a Delphi survey to assess the utility of preclinical models, including animal and cell-based models, in elucidating the causal role of the gut microbiome in these diseases. The Delphi survey aimed to address the complexity of selecting appropriate preclinical models to investigate disease causality and to study host–microbiome interactions effectively. We adopted a structured approach encompassing a literature review, expert workshops and the Delphi questionnaire to gather insights from a diverse range of stakeholders. Experts were requested to evaluate the strengths, limitations, and suitability of these models in addressing the causal relationship between the gut microbiome and disease pathogenesis. The resulting consensus statements and recommendations provide valuable insights for selecting preclinical models in future studies of gut microbiome-related diseases.
CRIS-Team Scopus Importer:2025-03-21

Born to be wild: utilizing natural microbiota for reliable biomedical research - Bruno, Philipp; Schüler, Thomas; Rosshart, Stephan Patrick (Trends in Immunology, 2025)
Laboratory mice housed under specific pathogen–free (SPF) conditions are the standard model in biomedical research. However, experiments with a particular inbred mouse strain performed in different laboratories often yield inconsistent or conflicting data due to housing-specific variations in the composition and diversity of SPF microbiota. These variations affect immune and nonimmune cell functions, leading to systemic physiological changes. Consequently, microbiota-dependent inconsistencies have raised general doubts regarding the suitability of mice as model organisms. Since stability positively correlates with biological diversity, we postulate that increasing species diversity can improve microbiota stability and mouse physiology, enhancing robustness, reproducibility, and experimental validity. Similar to the generation of inbred mouse strains in the last century, we suggest a worldwide initiative to define a transplantable ‘wild’ microbiota that stably colonizes mice irrespective of housing conditions.
CRIS-Team Scopus Importer:2025-02-17
Keywords: activation threshold; dirty mice; metaorganism; natural microbiota; reproducibility; standardization; translational mouse models; wildlings

Burrowing Behavior as Robust Parameter for Early Humane Endpoint Determination in Murine Models for Pancreatic Cancer - Brandstetter, Jakob; Hoffmann, Lisa; Koopmann, Ingo; Schreiber, Tim; Schulz, Benjamin; Rosshart, Stephan Patrick; Zechner, Dietmar; Vollmar, Brigitte; Kumstel, Simone (Animals, 2025)
In vivo experiments remain essential for testing new therapeutic approaches against fatal diseases, such as pancreatic cancer. Laws and regulations mandate the continuous improvement of the animal’s welfare during these experiments. One important aspect is the definition of early humane endpoint criteria to prevent the severe suffering of mice through timely euthanasia. In the present study, the welfare of mice in different pancreatic cancer models, and after various treatments for testing their preclinical efficacy, was monitored using body weight change, distress score, perianal temperature, burrowing behavior, nesting activity, and the mouse grimace scale. The ability of each parameter to predict the humane endpoint for each mouse was retrospectively quantified using receiver operating characteristic curve analysis. Burrowing behavior proved to be a robust predictor of the humane endpoint across all different pancreatic cancer models and treatment groups.
CRIS-Team Scopus Importer:2025-05-23
Keywords: animal welfare; early humane endpoint; pancreatic cancer; refinement

Circulating NK cells establish tissue residency upon acute infection of skin and mediate accelerated effector responses to secondary infection - Torcellan, Tommaso; Friedrich, Christin; Doucet-Ladevèze, Rémi; Ossner, Thomas; Solé, Virgínia Visaconill; Riedmann, Sofie; Ugur, Milas; Imdahl, Fabian; Rosshart, Stephan Patrick; Arnold, Sebastian J.; Gomez de Agüero, Mercedes; Gagliani, Nicola; et al. (Immunity, 2024)
Natural killer (NK) cells are present in the circulation and can also be found residing in tissues, and these populations exhibit distinct developmental requirements and are thought to differ in terms of ontogeny. Here, we investigate whether circulating conventional NK (cNK) cells can develop into long-lived tissue-resident NK (trNK) cells following acute infections. We found that viral and bacterial infections of the skin triggered the recruitment of cNK cells and their differentiation into Tcf1hiCD69hi trNK cells that share transcriptional similarity with CD56brightTCF1hi NK cells in human tissues. Skin trNK cells arose from interferon (IFN)-γ-producing effector cells and required restricted expression of the transcriptional regulator Blimp1 to optimize Tcf1-dependent trNK cell formation. Upon secondary infection, trNK cells rapidly gained effector function and mediated an accelerated NK cell response. Thus, cNK cells redistribute and permanently position at sites of previous infection via a mechanism promoting tissue residency that is distinct from Hobit-dependent developmental paths of NK cells and ILC1 seeding tissues during ontogeny.
CRIS-Team Scopus Importer:2024-01-19
Keywords: infection; innate immune memory; innate lymphoid cells; natural killer cells; Staphylococcus aureus; tissue immunity; tissue-resident lymphocytes; trained immunity; vaccination; vaccinia virus

Discovery of several thousand highly diverse circular DNA viruses - Tisza, Michael J.; Pastrana, Diana V.; Welch, Nicole L.; Stewart, Brittany; Peretti, Alberto; Starrett, Gabriel J.; Pang, Yuk-Ying S.; Krishnamurthy, Siddharth R.; Pesavento, Patricia A.; Mcdermott, David H.; Murphy, Philip M.; Whited, Jessica L.; et al. (eLife, 2020)
Although millions of distinct virus species likely exist, only approximately 9000 are catalogued in GenBank’s RefSeq database. We selectively enriched for the genomes of circular DNA viruses in over 70 animal samples, ranging from nematodes to human tissue specimens. A bioinformatics pipeline, Cenote-Taker, was developed to automatically annotate over 2500 complete genomes in a GenBank-compliant format. The new genomes belong to dozens of established and emerging viral families. Some appear to be the result of previously undescribed recombination events between ssDNA and ssRNA viruses. In addition, hundreds of circular DNA elements that do not encode any discernable similarities to previously characterized sequences were identified. To characterize these ‘dark matter’ sequences, we used an artificial neural network to identify candidate viral capsid proteins, several of which formed virus-like particles when expressed in culture. These data further the understanding of viral sequence diversity and allow for high throughput documentation of the virosphere.
CRIS-Team Scopus Importer:2022-12-14

Drug-induced liver injury Arzneimitteltoxische hepatopathie - Rosshart, Stephan Patrick; Spangenberg, Hans Christian (Arzneimitteltherapie, 2011)
Drug induced liver injury (DILI) has become a serious health issue. Generally, drug induced liver injuries can be classified as being intrinsic (predictable) or idiosyncratic (non-predictable), the latter type being by far the most common. The incidence rate of DILI is estimated at about 13.9 per 100.000 inhabitants. While further research is still needed to obtain a better understanding of the pathogenesis of the idiosyncratic DILI, a number of genetic and non-genetic risk factors have already been identified. However, since genetic risk factors do not allow a prediction of the patients' risk for DILI so far, the identification of non-genetic risk factors is essential in clinical practice. The clinical manifestation, histology and laboratory results of DILI can mimic almost any form of acute and chronic liver disease. Therefore, other liver diseases have to be excluded prior the diagnosis of DILI, however the key to a successful diagnosis is a thorough anamnesis. Though DILI is diagnosed per exclusionem, the experienced clinician should generally be able to choose the appropriate primary diagnostic method. Currently, methodologies to assess the causality between medication and drug induced liver injury are being optimized. RUCAM is presently the most widely-used method and can be regarded as state-of-the-art. Antibiotics, analgesic and NSAIDs are among those drugs that are most frequently related to drug induced liver injuries. In view of the fact that many patients turn to complementary and alternative medicine, herbal drugs, dietary supplements - such as weight loss and muscle building supplements - and other over-the-counter agents, the effects of these substances should also be considered as triggers and or causes of DILI. The prognosis of DILI is in general good, since in most cases a full recovery is achieved. However severe cases leading to liver transplantation or death can occur. Chronic liver disease as a consequence of DILI has been reported to occur in approximately 3-6% of patients with DILI. Total bilirubin and AST levels are the most reliable predictors for a severe course of the disease leading to a high mortality and transplantation rate. Identifying and discontinuing the causative agent is considered to be the most effective therapeutic measure. Glucocorticoids may be effective when systemic immunoreactions are detectable, however no studies have evaluated their effect on disease progression so far. In summary, the diagnosis und treatment of DILI remains a challenging problem for clinicians, researchers and the pharmaceutical industry.
CRIS-Team Scopus Importer:2022-12-14
Keywords: CIOMS/RUCAM scale; DILI; Drug-induced liver injury; Hepatotoxicity

Gut-to-brain spreading of pathology in synucleinopathies: A focus on molecular signalling mediators - Schmitt, Verena; Masanetz, Rebecca Katharina; Weidenfeller, Martin; Ebbinghaus, Lara Savannah; Süß, Patrick; Rosshart, Stephan Patrick; von Hörsten, Stephan; Zunke, Friederike; Winkler, Jürgen; Xiang, Wei (Behavioural Brain Research, 2023)
Synucleinopathies are a group of neurodegenerative disorders, classically characterized by the accumulation of aggregated alpha synuclein (aSyn) in the central nervous system. Parkinson's disease (PD) and multiple system atrophy (MSA) are the two prominent members of this family. Current treatment options mainly focus on the motor symptoms of these diseases. However, non-motor symptoms, including gastrointestinal (GI) symptoms, have recently gained particular attention, as they are frequently associated with synucleinopathies and often arise before motor symptoms. The gut-origin hypothesis has been proposed based on evidence of an ascending spreading pattern of aggregated aSyn from the gut to the brain, as well as the comorbidity of inflammatory bowel disease and synucleinopathies. Recent advances have shed light on the mechanisms underlying the progression of synucleinopathies along the gut-brain axis. Given the rapidly expanding pace of research in the field, this review presents a summary of the latest findings on the gut-to-brain spreading of pathology and potential pathology-reinforcing mediators in synucleinopathies. Here, we focus on 1) gut-to-brain communication pathways, including neuronal pathways and blood circulation, and 2) potential molecular signalling mediators, including bacterial amyloid proteins, microbiota dysbiosis-induced alterations in gut metabolites, as well as host-derived effectors, including gut-derived peptides and hormones. We highlight the clinical relevance and implications of these molecular mediators and their possible mechanisms in synucleinopathies. Moreover, we discuss their potential as diagnostic markers in distinguishing the subtypes of synucleinopathies and other neurodegenerative diseases, as well as for developing novel individualized therapeutic options for synucleinopathies.
CRIS-Team Scopus Importer:2023-08-25
Keywords: Alpha synuclein; Gut-to-brain communication; Inflammatory bowel disease; Multiple system atrophy; Parkinson's disease

GVHD, IBD, and primary immunodeficiencies: The gut as a target of immunopathology resulting from impaired immunity - Zeiser, Robert; Warnatz, Klaus; Rosshart, Stephan Patrick; Sagar; Tanriver, Yakup (European Journal of Immunology, 2022)
The intestinal tract is the largest immunological organ in the body and has a central function of regulating local immune responses, as the intestinal epithelial barrier is a location where the immune system interacts with the gut microbiome including bacteria, fungi, and viruses. Impaired immunity in the intestinal tract can lead to immunopathology, which manifests in different diseases such as inflammatory bowel disease or intestinal graft-versus-host disease. A disturbed communication between epithelial cells, immune cells, and microbiome will shape pathogenic immune responses to antigens, which need to be counterbalanced by tolerogenic mechanisms and repair mechanisms. Here, we review how impaired intestinal immune function leads to immunopathology with a specific focus on innate immune cells, the role of the microbiome, and the resulting clinical manifestations including intestinal graft-versus-host disease, inflammatory bowel disease, and enteropathy in primary immunodeficiency.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Graft-versus-host disease; Inflammatory bowel disease; Microbiome; Primary immunodeficiency

Human resident liver myeloid cells protect against metabolic stress in obesity - Barreby, Emelie; Strunz, Benedikt; Nock, Sebastian; Naudet, Léa; Shen, Joanne X.; Johansson, Helene; Sönnerborg, Isabella; Ma, Junjie; Urgard, Egon; Pallett, Laura J.; Hu, Yizhou; Fardellas, Achilleas; et al. (Nature Metabolism, 2023)
Although multiple populations of macrophages have been described in the human liver, their function and turnover in patients with obesity at high risk of developing non-alcoholic fatty liver disease (NAFLD) and cirrhosis are currently unknown. Herein, we identify a specific human population of resident liver myeloid cells that protects against the metabolic impairment associated with obesity. By studying the turnover of liver myeloid cells in individuals undergoing liver transplantation, we find that liver myeloid cell turnover differs between humans and mice. Using single-cell techniques and flow cytometry, we determine that the proportion of the protective resident liver myeloid cells, denoted liver myeloid cells 2 (LM2), decreases during obesity. Functional validation approaches using human 2D and 3D cultures reveal that the presence of LM2 ameliorates the oxidative stress associated with obese conditions. Our study indicates that resident myeloid cells could be a therapeutic target to decrease the oxidative stress associated with NAFLD.
CRIS-Team Scopus Importer:2023-07-21

Impact of High Salt-Intake on a Natural Gut Ecosystem in Wildling Mice - Cardilli, Alessio; Hamad, Ibrahim; Dyczko, Aleksandra; Thijs, Sofie; Vangronsveld, Jaco; Müller, Dominik N.; Rosshart, Stephan Patrick; Kleinewietfeld, Markus (Nutrients, 2023)
The mammalian holobiont harbors a complex and interdependent mutualistic gut bacterial community. Shifts in the composition of this bacterial consortium are known to be a key element in host health, immunity and disease. Among many others, dietary habits are impactful drivers for a potential disruption of the bacteria-host mutualistic interaction. In this context, we previously demonstrated that a high-salt diet (HSD) leads to a dysbiotic condition of murine gut microbiota, characterized by a decrease or depletion of well-known health-promoting gut bacteria. However, due to a controlled and sanitized environment, conventional laboratory mice (CLM) possess a less diverse gut microbiota compared to wild mice, leading to poor translational outcome for gut microbiome studies, since a reduced gut microbiota diversity could fail to depict the complex interdependent networks of the microbiome. Here, we evaluated the HSD effect on gut microbiota in CLM in comparison to wildling mice, which harbor a natural gut ecosystem more closely mimicking the situation in humans. Mice were treated with either control food or HSD and gut microbiota were profiled using amplicon-based methods targeting the 16S ribosomal gene. In line with previous findings, our results revealed that HSD induced significant loss of alpha diversity and extensive modulation of gut microbiota composition in CLM, characterized by the decrease in potentially beneficial bacteria from Firmicutes phylum such as the genera Lactobacillus, Roseburia, Tuzzerella, Anaerovorax and increase in Akkermansia and Parasutterella. However, HSD-treated wildling mice did not show the same changes in terms of alpha diversity and loss of Firmicutes bacteria as CLM, and more generally, wildlings exhibited only minor shifts in the gut microbiota composition upon HSD. In line with this, 16S-based functional analysis suggested only major shifts of gut microbiota ecological functions in CLM compared to wildling mice upon HSD. Our findings indicate that richer and wild-derived gut microbiota is more resistant to dietary interventions such as HSD, compared to gut microbiota of CLM, which may have important implications for future translational microbiome research.
CRIS-Team Scopus Importer:2023-04-21
Keywords: high-salt diet; immunity; microbiome; wildling

Keratinocyte-intrinsic MHCII expression controls microbiota-induced Th1 cell responses - Tamoutounour, Samira; Han, Seong-Ji; Deckers, Julie; Constantinides, Michael G.; Hurabielle, Charlotte; Harrison, Oliver J.; Bouladoux, Nicolas; Linehan, Jonathan L.; Link, Verena M.; Vujkovic-Cvijin, Ivan; Perez-Chaparro, Paula Juliana; Rosshart, Stephan P.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2019)
The cross-talk between the microbiota and the immune system plays a fundamental role in the control of host physiology. However, the tissue-specific factors controlling this dialogue remain poorly understood. Here we demonstrate that T cell responses to commensal colonization are associated with the development of organized cellular clusters within the skin epithelium. These organized lymphocyte clusters are surrounded by keratinocytes expressing a discrete program associated with antigen presentation and antimicrobial defense. Notably, IL-22–mediated keratinocyte-intrinsic MHC class II expression was required for the selective accumulation of commensal-induced IFN-γ, but not IL-17A–producing CD4+ T cells within the skin. Taking these data together, this work uncovers an unexpected role for MHC class II expression by keratinocytes in the control of homeostatic type 1 responses to the microbiota. Our findings have important implications for the understanding of the tissue-specific rules governing the dialogue between a host and its microbiota.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Antigen presentation; Keratinocyte; Microbiota; Skin; Th1

Laboratory mice born to wild mice have natural microbiota and model human immune responses - Rosshart, Stephan P.; Herz, Jasmin; Vassallo, Brian G.; Hunter, Ashli; Wall, Morgan K.; Badger, Jonathan H.; Mcculloch, John A.; Anastasakis, Dimitrios G.; Sarshad, Aishe A.; Leonardi, Irina; Collins, Nicholas; Blatter, Joshua A.; et al. (Science, 2019)
Laboratory mouse studies are paramount for understanding basic biological phenomena but also have limitations. These include conflicting results caused by divergent microbiota and limited translational research value. To address both shortcomings, we transferred C57BL/6 embryos into wild mice, creating “wildlings.” These mice have a natural microbiota and pathogens at all body sites and the tractable genetics of C57BL/6 mice. The bacterial microbiome, mycobiome, and virome of wildlings affect the immune landscape of multiple organs. Their gut microbiota outcompete laboratory microbiota and demonstrate resilience to environmental challenges. Wildlings, but not conventional laboratory mice, phenocopied human immune responses in two preclinical studies. A combined natural microbiota- and pathogen-based model may enhance the reproducibility of biomedical studies and increase the bench-to-bedside safety and success of immunological studies.
CRIS-Team Scopus Importer:2022-12-14

Laboratory mice with a wild microbiota generate strong allergic immune responses - Ma, Junjie; Urgard, Egon; Runge, Solveig; Classon, Cajsa H.; Mathä, Laura; Stark, Julian M.; Cheng, Liqin; Álvarez, Javiera A.; von Zedtwitz, Silvia; Baleviciute, Austeja; Hoyer, Sergio Martinez; Li, Muzhen; et al. (Science immunology, 2023)
Allergic disorders are caused by a combination of hereditary and environmental factors. The hygiene hypothesis postulates that early-life microbial exposures impede the development of subsequent allergic disease. Recently developed "wildling"mice are genetically identical to standard laboratory specific pathogen-free (SPF) mice but are housed under seminatural conditions and have rich microbial exposures from birth. Thus, by comparing conventional SPF mice with wildlings, we can uncouple the impact of lifelong microbial exposures from genetic factors on the allergic immune response. We found that wildlings developed larger populations of antigen-experienced T cells than conventional SPF mice, which included interleukin-10-producing CD4 T cells specific for commensal Lactobacilli strains and allergy-promoting T helper 2 (TH2) cells. In models of airway exposure to house dust mite (HDM), recombinant interleukin-33, or Alternaria alternata, wildlings developed strong allergic inflammation, characterized by eosinophil recruitment, goblet cell metaplasia, and antigen-specific immunoglobulin G1 (IgG1) and IgE responses. Wildlings developed robust de novo TH2 cell responses to incoming allergens, whereas preexisting TH2 cells could also be recruited into the allergic immune response in a cytokinedriven and TCR-independent fashion. Thus, wildling mice, which experience diverse and lifelong microbial exposures, were not protected from developing pathological allergic immune responses. Instead, wildlings mounted robust allergic responses to incoming allergens, shedding new light on the hygiene hypothesis.
CRIS-Team Scopus Importer:2024-12-16

M cell maturation and cDC activation determine the onset of adaptive immune priming in the neonatal Peyer's patch - Torow, Natalia; Li, Ronghui; Hitch, Thomas Charles Adrian; Mingels, Clemens; Al Bounny, Shahed; van Best, Niels; Stange, Eva Lena; Simons, Britta; Maié, Tiago; Rüttger, Lennart; Gubbi, Narasimha Murthy Keshava Prasad; Abbott, Darryl Adelaide; et al. (Immunity, 2023)
Early-life immune development is critical to long-term host health. However, the mechanisms that determine the pace of postnatal immune maturation are not fully resolved. Here, we analyzed mononuclear phagocytes (MNPs) in small intestinal Peyer's patches (PPs), the primary inductive site of intestinal immunity. Conventional type 1 and 2 dendritic cells (cDC1 and cDC2) and RORgt+ antigen-presenting cells (RORgt+ APC) exhibited significant age-dependent changes in subset composition, tissue distribution, and reduced cell maturation, subsequently resulting in a lack in CD4+ T cell priming during the postnatal period. Microbial cues contributed but could not fully explain the discrepancies in MNP maturation. Type I interferon (IFN) accelerated MNP maturation but IFN signaling did not represent the physiological stimulus. Instead, follicle-associated epithelium (FAE) M cell differentiation was required and sufficient to drive postweaning PP MNP maturation. Together, our results highlight the role of FAE M cell differentiation and MNP maturation in postnatal immune development.
CRIS-Team Scopus Importer:2023-06-23
Keywords: cDC2; dendritic cell; M cell; microbiota; neonatal immunology; Peyer's patch; post-natal establishment of intestinal homeostasis; RORgt

Neonatal exposure to a wild-derived microbiome protects mice against diet-induced obesity - Hild, Benedikt; Dreier, Matthew S.; Oh, Ji Hoon; Mcculloch, John A.; Badger, Jonathan H.; Guo, Juen; Thefaine, Claire E.; Umarova, Regina; Hall, Kevin D.; Gavrilova, Oksana; Rosshart, Stephan P.; Trinchieri, Giorgio; et al. (Nature Metabolism, 2021)
Obesity and its consequences are among the greatest challenges in healthcare. The gut microbiome is recognized as a key factor in the pathogenesis of obesity. Using a mouse model, we show here that a wild-derived microbiome protects against excessive weight gain, severe fatty liver disease and metabolic syndrome during a 10-week course of high-fat diet. This phenotype is transferable only during the first weeks of life. In adult mice, neither transfer nor severe disturbance of the wild-type microbiome modifies the metabolic response to a high-fat diet. The protective phenotype is associated with increased secretion of metabolic hormones and increased energy expenditure through activation of brown adipose tissue. Thus, we identify a microbiome that protects against weight gain and its negative consequences through metabolic programming in early life. Translation of these results to humans may identify early-life therapeutics that protect against obesity.
CRIS-Team Scopus Importer:2022-12-14

Non-classical Immunity Controls Microbiota Impact on Skin Immunity and Tissue Repair - Linehan, Jonathan L.; Harrison, Oliver J.; Han, Seong-Ji; Byrd, Allyson L.; Vujkovic-Cvijin, Ivan; Villarino, Alejandro V.; Sen, Shurjo K.; Shaik, Jahangheer; Smelkinson, Margery; Tamoutounour, Samira; Collins, Nicholas; Bouladoux, Nicolas; et al. (Cell, 2018)
Mammalian barrier surfaces are constitutively colonized by numerous microorganisms. We explored how the microbiota was sensed by the immune system and the defining properties of such responses. Here, we show that a skin commensal can induce T cell responses in a manner that is restricted to non-classical MHC class I molecules. These responses are uncoupled from inflammation and highly distinct from pathogen-induced cells. Commensal-specific T cells express a defined gene signature that is characterized by expression of effector genes together with immunoregulatory and tissue-repair signatures. As such, non-classical MHCI-restricted commensal-specific immune responses not only promoted protection to pathogens, but also accelerated skin wound closure. Thus, the microbiota can induce a highly physiological and pleiotropic form of adaptive immunity that couples antimicrobial function with tissue repair. Our work also reveals that non-classical MHC class I molecules, an evolutionarily ancient arm of the immune system, can promote homeostatic immunity to the microbiota. Microbiota induce a form of adaptive immunity that couples antimicrobial function with tissue repair.
CRIS-Team Scopus Importer:2022-12-14
Keywords: H2-M3; MHCIb; microbiota; non-classical MHC class I; skin immunity; Staphylococcus epidermidis; tissue repair

Proteolytic processing of galectin-3 by meprin metalloproteases is crucial for host-microbiome homeostasis - Bülck, Cynthia; Nyström, Elisabeth E.L.; Koudelka, Tomas; Mannbar-Frahm, Michael; Andresen, Gerrit; Radhouani, Mariem; Tran, Florian; Scharfenberg, Franka; Schrell, Friederike; Armbrust, Fred; Dahlke, Eileen; Zhao, Bei; et al. (Science Advances, 2023)
The metalloproteases meprin α and meprin β are highly expressed in the healthy gut but significantly decreased in inflammatory bowel disease, implicating a protective role in mucosal homeostasis. In the colon, meprin α and meprin β form covalently linked heterodimers tethering meprin α to the plasma membrane, therefore presenting dual proteolytic activity in a unique enzyme complex. To unravel its function, we applied N-terminomics and identified galectin-3 as the major intestinal substrate for meprin α/β heterodimers. Galectin-3-deficient and meprin α/β double knockout mice show similar alterations in their microbiome in comparison to wild-type mice. We further demonstrate that meprin α/β heterodimers differentially process galectin-3 upon bacterial infection, in germ-free, conventionally housed (specific pathogen-free), or wildling mice, which in turn regulates the bacterial agglutination properties of galectin-3. Thus, the constitutive cleavage of galectin-3 by meprin α/β heterodimers may play a key role in colon host-microbiome homeostasis.
CRIS-Team Scopus Importer:2023-04-14

R2d2 Drives Selfish Sweeps in the House Mouse - Didion, John P.; Morgan, Andrew P.; Yadgary, Liran; Bell, Timothy A.; Mcmullan, Rachel C.; De Solorzano, Lydia Ortiz; Britton-Davidian, Janice; Bult, Carol J.; Campbell, Karl J.; Castiglia, Riccardo; Ching, Yung-Hao; Chunco, Amanda J.; et al. (Molecular Biology and Evolution, 2016)
A selective sweep is the result of strong positive selection driving newly occurring or standing genetic variants to fixation, and can dramatically alter the pattern and distribution of allelic diversity in a population. Population-level sequencing data have enabled discoveries of selective sweeps associated with genes involved in recent adaptations in many species. In contrast, much debate but little evidence addresses whether "selfish" genes are capable of fixation - thereby leaving signatures identical to classical selective sweeps - despite being neutral or deleterious to organismal fitness. We previously described R2d2, a large copy-number variant that causes nonrandom segregation of mouse Chromosome 2 in females due to meiotic drive. Here we show population-genetic data consistent with a selfish sweep driven by alleles of R2d2 with high copy number (R2d2HC) in natural populations. We replicate this finding in multiple closed breeding populations from six outbred backgrounds segregating for R2d2 alleles. We find that R2d2HC rapidly increases in frequency, and in most cases becomes fixed in significantly fewer generations than can be explained by genetic drift. R2d2HC is also associated with significantly reduced litter sizes in heterozygous mothers, making it a true selfish allele. Our data provide direct evidence of populations actively undergoing selfish sweeps, and demonstrate that meiotic drive can rapidly alter the genomic landscape in favor of mutations with neutral or even negative effects on overall Darwinian fitness. Further study will reveal the incidence of selfish sweeps, and will elucidate the relative contributions of selfish genes, adaptation and genetic drift to evolution.
CRIS-Team Scopus Importer:2022-12-14
Keywords: House Mouse; Meiotic Drive; R2d2; Selective Sweep; Selfish Genes

Reactive oxygen species regulate early development of the intestinal macrophage-microbiome interface - Mansoori Moghadam, Zohreh; Zhao, Bei; Raynaud, Candice; Strohmeier, Valentina; Neuber, Jana; Lösslein, Anne Kathrin; Qureshi, Sabrina; Gres, Vitka; Ziegelbauer, Tara; Baasch, Sebastian; Schell, Christoph; Warnatz, Klaus; et al. (Blood, 2025)
The controlled development of cellular intestinal immunity in the face of dynamic microbiota emergence constitutes a major challenge in very early life and is a bottleneck for sustained growth and well-being. Early-onset inflammatory bowel disease (IBD) represents an extreme disturbance of intestinal immunity. It is a hallmark and often the first manifestation of chronic granulomatous disease (CGD), caused by inborn defects in the nicotinamide adenine dinucleotide phosphate oxidase 2 (NOX2) in phagocytes and thus the failure to produce reactive oxygen species (ROS). However, in contrast to the known role of ROS in antimicrobial defense, the mechanisms underlying intestinal immunopathology in CGD remain enigmatic. This is partly due to the incomplete recapitulation of the CGD-IBD phenotype in established mouse models. We found that mice deficient in the NOX2 subunits p47phox or gp91phox showed similar baseline disturbances in lamina propria macrophage differentiation but responded differently to chemically induced colitis. Although p47phox- and gp91phox-deficient mice differed markedly in microbiota composition, crossfostering failed to equalize discrepant IBD phenotypes and microbiota, pointing at extremely early and functionally important microbiota fixation under specific pathogen-free housing conditions. In contrast, neonatal acquisition of a complex wild-mouse microbiota triggered spontaneous IBD, granuloma formation, and secondary sepsis with intestinal pathogens in both NOX2-deficient mouse lines, which was in part dependent on NOX2 in intestinal macrophages. Thus, in experimental CGD, the aberrant development of tissue immunity and microbiota are closely intertwined immediately after birth.
CRIS-Team Scopus Importer:2025-03-14

Systemic toxoplasma infection triggers a long-term defect in the generation and function of naive T lymphocytes - Kugler, David G.; Flomerfelt, Francis A.; Costa, Diego L.; Laky, Karen; Kamenyeva, Olena; Mittelstadt, Paul R.; Gress, Ronald E.; Rosshart, Stephan P.; Rehermann, Barbara; Ashwell, Jonathan D.; Sher, Alan; Jankovic, Dragana (Journal of Experimental Medicine, 2016)
Because antigen-stimulated naive T cells either die as effectors or enter the activated/memory pool, continuous egress of new T lymphocytes from thymus is essential for maintenance of peripheral immune homeostasis. Unexpectedly, we found that systemic infection with the protozoan Toxoplasma gondii triggers not only a transient increase in activated CD4+ Th1 cells but also a persistent decrease in the size of the naive CD4+ T lymphocyte pool. This immune defect is associated with decreased thymic output and parasite-induced destruction of the thymic epithelium, as well as disruption of the overall architecture of that primary lymphoid organ. Importantly, the resulting quantitative and qualitative deficiency in naive CD4+ T cells leads to an immunocompromised state that both promotes chronic toxoplasma infection and leads to decreased resistance to challenge with an unrelated pathogen. These findings reveal that systemic infectious agents, such as T. gondii, can induce long-term immune alterations associated with impaired thymic function. When accumulated during the lifetime of the host, such events, even when occurring at low magnitude, could be a contributing factor in immunological senescence.
CRIS-Team Scopus Importer:2022-12-14

The Gut Microbiome in Hypertension: Recent Advances and Future Perspectives - Avery, Ellen G.; Bartolomaeus, Hendrik; Maifeld, Andras; Marko, Lajos; Wiig, Helge; Wilck, Nicola; Rosshart, Stephan Patrick; Forslund, Sofia K.; Mueller, Dominik N. (Circulation Research, 2021)
The pathogenesis of hypertension is known to involve a diverse range of contributing factors including genetic, environmental, hormonal, hemodynamic and inflammatory forces, to name a few. There is mounting evidence to suggest that the gut microbiome plays an important role in the development and pathogenesis of hypertension. The gastrointestinal tract, which houses the largest compartment of immune cells in the body, represents the intersection of the environment and the host. Accordingly, lifestyle factors shape and are modulated by the microbiome, modifying the risk for hypertensive disease. One well-studied example is the consumption of dietary fibers, which leads to the production of short-chain fatty acids and can contribute to the expansion of anti-inflammatory immune cells, consequently protecting against the progression of hypertension. Dietary interventions such as fasting have also been shown to impact hypertension via the microbiome. Studying the microbiome in hypertensive disease presents a variety of unique challenges to the use of traditional model systems. Integrating microbiome considerations into preclinical research is crucial, and novel strategies to account for reciprocal host-microbiome interactions, such as the wildling mouse model, may provide new opportunities for translation. The intricacies of the role of the microbiome in hypertensive disease is a matter of ongoing research, and there are several technical considerations which should be accounted for moving forward. In this review we provide insights into the host-microbiome interaction and summarize the evidence of its importance in the regulation of blood pressure. Additionally, we provide recommendations for ongoing and future research, such that important insights from the microbiome field at large can be readily integrated in the context of hypertension.
CRIS-Team Scopus Importer:2022-12-14
Keywords: blood pressure; fasting; fatty acids; volatile; hypertension; immune system; microbiota; translational medical research

The Mammalian Metaorganism: A Holistic View on How Microbes of All Kingdoms and Niches Shape Local and Systemic Immunity - Runge, Solveig; Rosshart, Stephan Patrick (Frontiers in Immunology, 2021)
The field of microbiome research has developed rapidly over the past decades and has become a topic of major interest to basic, preclinical, and clinical research, the pharmaceutical industry as well as the general public. The microbiome is a complex and diverse ecosystem and defined as the collection of all host-associated microorganisms and their genes. It is acquired through vertical transmission and environmental exposure and includes microbes of all kingdoms: bacteria, archaea, prokaryotic and eukaryotic viruses, fungi, protozoa, and the meiofauna. These microorganisms co-evolved with their respective hosts over millions of years, thereby establishing a mutually beneficial, symbiotic relationship on all epithelial barriers. Thus, the microbiome plays a pivotal role in virtually every aspect of mammalian physiology, particularly in the development, homeostasis, and function of the immune system. Consequently, the combination of the host genome and the microbial genome, together referred to as the metagenome, largely drives the mammalian phenotype. So far, the majority of studies have unilaterally focused on the gastrointestinal bacterial microbiota. However, recent work illustrating the impact of viruses, fungi, and protozoa on host immunity urges us towards a holistic view of the mammalian microbiome and the appreciation for its non-bacterial kingdoms. In addition, the importance of microbiota on epithelial barriers other than the gut as well as their systemic effects via microbially-derived biologically active compounds is increasingly recognized. Here, we want to provide a brief but comprehensive overview of the most important findings and the current knowledge on how microbes of all kingdoms and microbial niches shape local and systemic immunity in health and disease.
CRIS-Team Scopus Importer:2022-12-14
Keywords: archaeome; bacterial microbiome; gut microbiota; lung microbiota; mycobiome; skin microbiota; vaginal microbiota; virome

The Microbiota-Gut-Brain Axis in Health and Disease and Its Implications for Translational Research - Schaechtle, Melanie Anna; Rosshart, Stephan Patrick (Frontiers in Cellular Neuroscience, 2021)
Over the past decades, microbiome research has evolved rapidly and became a hot topic in basic, preclinical and clinical research, for the pharmaceutical industry and for the general public. With the help of new high-throughput sequencing technologies tremendous progress has been made in the characterization of host-microbiota interactions identifying the microbiome as a major factor shaping mammalian physiology. This development also led to the discovery of the gut-brain axis as the crucial connection between gut microbiota and the nervous system. Consequently, a rapidly growing body of evidence emerged suggesting that the commensal gut microbiota plays a vital role in brain physiology. Moreover, it became evident that the communication along this microbiota-gut-brain axis is bidirectional and primarily mediated by biologically active microbial molecules and metabolites. Further, intestinal dysbiosis leading to changes in the bidirectional relationship between gut microbiota and the nervous system was linked to the pathogenesis of several psychiatric and neurological disorders. Here, we discuss the impact of the gut microbiota on the brain in health and disease, specifically as regards to neuronal homeostasis, development and normal aging as well as their role in neurological diseases of the highest socioeconomic burden such as Alzheimer’s disease and stroke. Subsequently, we utilize Alzheimer’s disease and stroke to examine the translational research value of current mouse models in the spotlight of microbiome research. Finally, we propose future strategies on how we could conduct translational microbiome research in the field of neuroscience that may lead to the identification of novel treatments for human diseases.
CRIS-Team Scopus Importer:2022-12-14
Keywords: Alzheimer’s disease; germ-free rodent; gut microbiota; gut-brain axis; microglia; short-chain fatty acids; stroke; wildling

Wild Mouse Gut Microbiota Promotes Host Fitness and Improves Disease Resistance - Rosshart, Stephan P.; Vassallo, Brian G.; Angeletti, Davide; Hutchinson, Diane S.; Morgan, Andrew P.; Takeda, Kazuyo; Hickman, Heather D.; Mcculloch, John A.; Badger, Jonathan H.; Ajami, Nadim J.; Trinchieri, Giorgio; De Villena, Fernando Pardo-Manuel; et al. (Cell, 2017)
Laboratory mice, while paramount for understanding basic biological phenomena, are limited in modeling complex diseases of humans and other free-living mammals. Because the microbiome is a major factor in mammalian physiology, we aimed to identify a naturally evolved reference microbiome to better recapitulate physiological phenomena relevant in the natural world outside the laboratory. Among 21 distinct mouse populations worldwide, we identified a closely related wild relative to standard laboratory mouse strains. Its bacterial gut microbiome differed significantly from its laboratory mouse counterpart and was transferred to and maintained in laboratory mice over several generations. Laboratory mice reconstituted with natural microbiota exhibited reduced inflammation and increased survival following influenza virus infection and improved resistance against mutagen/inflammation-induced colorectal tumorigenesis. By demonstrating the host fitness-promoting traits of natural microbiota, our findings should enable the discovery of protective mechanisms relevant in the natural world and improve the modeling of complex diseases of free-living mammals. Video Abstract Characterization of a wild mice reference microbiome opens a window of opportunity to understand how the gut microbiota affects aspects of host physiology that are important in the natural world outside the laboratory.
CRIS-Team Scopus Importer:2022-12-14
Keywords: bacteria; colorectal cancer; cytokine; gut; inflammation; influenza; innate; microbiome; virus; wild mouse